ARE WE RE-MARGINALIZING DISTANCE EDUCATION STUDENTS AND TEACHERS? - Thompson, Melody M. (Online Learning, 2007)
Changes in the language we use to talk about our activities in service of this mission and a concomitant increased emphasis on blended learning are two trends that emphasize the importance retaining important meaning and knowledge associated with earlier practice and do not limit our thinking by unnecessarily circumscribed discourse. Educators should keep an intentional awareness of the “distance” inherent in the activities and a focus on the multidimensional nature of “education,” which includes but is hardly coterminus with “learning.”